Efficacy of a fasting‐mimicking diet in functional therapy for depression: A randomised controlled pilot trial. Issue 10 (11th May 2020) - Maniaci, Giuseppe; La Cascia, Caterina; Giammanco, Alessandra; Ferraro, Laura; Chianetta, Roberta; Di Peri, Roberta; Sardella, Zaira; Citarrella, Roberto; Mannella, Yuri; Larcan, Stefania; Montana, Simonetta; Mirisola, Mario G.; et al.
Abstract: Objective: This randomized controlled trial examined the efficacy of adding a fasting‐mimicking diet to a structured psychotherapy protocol for treating depression. Design: Of 20 patients with depression, 10 were randomly assigned to psychotherapy and dieting (i.e., experimental group) and the other 10 to psychotherapy only (i.e., control group). Patients in both groups received 20 individual sessions of functional therapy along with nutrition consultation. Patients in the control group were instructed to maintain their usual daily diets. Results: Both treatments were effective in reducing depression as well as increasing self‐esteem and quality of life. The experimental group showed improved self‐esteem and psychological quality of life as well as a reduction in their mean body mass index, in comparison to the control group. Conclusions: The study revealed initial evidence of the efficacy of combining psychotherapy with a fasting‐mimicking diet to treat depression and its correlates.